There and back again: What the Cold War for Southeast Asia can teach us about Sino-US competition in the region today - NGOEI, Wen-Qing (Institutional Knowledge at Singapore Management University, 2019)
Expert commentary today typically focuses on the agendas and actions of the two big powers, the United States and China, which misses the bigger picture. During the Cold War, leaders of ASEAN (Association of Southeast Asian Nations) played a critical role in containing Chinese influence, shaping the terms of Sino-U.S. competition and rapprochement, and deepening the U.S. presence in Southeast Asia. The legacy of ASEAN’s foreign relations during and since the Cold War militates against the popular notion that Chinese hegemony in Asia is inevitable.